MARKETING MIX FRAMEWORKS THAT OPTIMIZE RETENTION RATES AND REDUCE CHURN IN SOFTWARE-AS-A-SERVICE (SAAS) BUSINESSES (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2026)
One major trend of the Software-as-a-Service (SaaS) industry is subscription-based service, meaning SaaS users are only in need of ongoing content based long-term profit depends more on the ability to keep their customers. Due to mounting customer acquisition expenses and growing competition, it has come to the forefront of SaaS companies' minds, therefore, churn reduction has become a strategic imperative in business models. This publication proposes an integrated marketing mix framework to mitigate churn and optimize customer retention for SaaS companies. Based on the classic 7Ps marketing mix model, this research develops a Retention-Oriented SaaS Marketing Mix (ROSMM) framework encompassing all aspects of product value optimization, pricing alignment, customer success-driven promotion, omnichannel service delivery, customer-centric processes, employee engagement and evidence-based performance management. The research offers a conceptual analysis based on recent SaaS retention literature illustrating how tactical alignment of marketing mix elements can be beneficial for CLV, NRR, customer satisfaction, and churn reduction. According to this study results indicated that SaaS companies utilizing retention-based marketing mix approach can enhance customer loyalty, recurring revenue streams and sustainable competitive edge.